On the relevance of an African Philosophy of Higher Education - Waghid, Y. (South African Journal of Higher Education, 2021)
Nowadays, higher educational theory seems to be concerned with positional thinking that reconsiders what universities ought to accomplish to justify their existence in the realm of higher education (Waghid and Davids, 2020). I want to extend this claim by arguing in defence of an African philosophy of higher education – one that is genuine and enframes higher education as a pedagogical space for resistance, critique, deliberative iterations, autonomy, and intellectual activism. Put differently, an African philosophy of higher education is one that is not only concerned with thinking and justification but expands into notions of democratic engagement, citizenship, and activism. When the latter are present, African philosophy of higher education has a real chance of manifesting ubiquitously in higher pedagogical actions, mostly teaching and learning. Only then, it possibly maintains its relevance to higher education discourses.